Terapia nutricional enteral: aspectos da assistência de enfermagem relevantes à auditoria de serviço - Paiva, Miriam Cristina Marque da Silva de [UNESP]; Juliani, Carmen Maria Casquel Monti [UNESP]; Lima, Silvana Andrea Molina [UNESP] (My University, 2014)
The aging population, increased severity of patients, delayed prescribing and failures in the implementation of nutritional therapy, compromise nutritional status of hospitalized patients. The Enteral Nutrition Therapy is a frequent practice as a strategy for preventing/treating malnutrition. Taken by simple therapy has several vulnerabilities in the process. Objective: To highlight the legislation and publications resulting from con- sensus, the main aspects of nursing in Enteral Nutrition Ther- apy applicable in services and auditable. Results: Among the aspects of the process of nursing work in TNE dimensions were addressed themes of "managing" and "caring". There was disagreement on the level of glycemic control and the question of gastric residue needs to be better resolved. We stress the importance of Systematization of Nursing Care, the organization of work, and the Nursing Process by directing the care and documentation, the audit process valuable practice. Considerations: It’s emphasized as a quality criterion, that practice must be validated scientifically, based on reasoned knowledge. As there are few scientific studies of recognized quality, consen- suses are useful. However, we must be judicious to support them because organizations are subject to political influences and industry publications may be distorted, resulting in high costs to the institution.

O envelhecimento da população, aumento da gravidade dos pacientes, atraso na indicação e falhas na implantação da terapia nutricional, comprometem o estado nutricional dos pacientes hospitalizados. A Terapia Nutricional Enteral é praticada frequentemente como estratégia para preve- nir/tratar desnutrição. Tomada por terapia simples, apre- senta vulnerabilidades devido às diversas etapas. Objetivo: destacar na legislação e publicações resultantes de consen- sos, os principais aspectos de enfermagem na Terapia Nutricional Enteral aplicáveis aos serviços e passíveis de au- ditoria. Resultados: Foram abordados temas das dimensões “gerenciar” e “cuidar”. Observou-se divergência quanto ao nível de controle da glicemia e a questão do resíduo gástrico precisa ser mais bem resolvida. Ressaltam-se a importância da Sistematização da Assistência de Enfermagem, na organização do trabalho, e do Processo de Enfermagem, orientando o cuidado e a documentação da prática, valiosos ao processo de auditoria. Reflexões: Enfatiza-se como critério de qualidade, que a prática deve ser validada cientificamente, baseada em conhecimento fundamentado. Como são poucos os estudos científicos de qualidade reconhecida, são úteis os consensos. No entanto, devemos ser criteriosos na adesão, pois organizações são passíveis de influências políticas e da indústria, podendo apresentar distorções nas publicações, ocasionando custos elevados à instituição.
Enteral nutrition therapy: relevant aspects of nursing care to service audit
Keywords: Enteral nutrition; Nursing; Audit; Nutrição enteral; Enfermagem; Auditoria